Resveratrol directly suppresses proteolysis possibly via PKA/CREB signaling in denervated rat skeletal muscle - IVANILDO I.S. JÚNIOR; GUSTAVO O. ZANETTI; TALES S. VIEIRA; FLÁVIA P. ALBUQUERQUE; DAYANE A. GOMES; SILVA PAULA-GOMES; RAFAEL R. VALENTIM; FLAVIA A. GRAÇA; ISIS C. KETTLHUT; LUIZ C.C. NAVEGANTES; DAWIT A.P. GONÇALVES; EDUARDO C. LIRA (Anais da Academia Brasileira de Ciências, 2023)
Abstract Although there are reports that polyphenol resveratrol (Rsv) may cause muscle hypertrophy in basal conditions and attenuate muscle wasting in catabolic situations, its mechanism of action is still unclear. Our study evaluated the ex vivo effects of Rsv on protein metabolism and intracellular signaling in innervated (sham-operated; Sham) and 3-day sciatic denervated (Den) rat skeletal muscles. Rsv (10-4 M) reduced total proteolysis (40%) in sham muscles. Den increased total proteolysis (~40%) in muscle, which was accompanied by an increase in the activities of ubiquitin-proteasome (~3-fold) and lysosomal (100%) proteolytic systems. Rsv reduced total proteolysis (59%) in Den muscles by inhibiting the hyperactivation of ubiquitin-proteasome (50%) and lysosomal (~70%) systems. Neither Rsv nor Den altered calcium-dependent proteolysis in muscles. Mechanistically, Rsv stimulated PKA/CREB signaling in Den muscles, and PKA blockage by H89 (50μM) abolished the antiproteolytic action of the polyphenol. Rsv reduced FoxO4 phosphorylation (~60%) in both Sham and Den muscles and Akt phosphorylation (36%) in Den muscles. Rsv also caused a homeostatic effect in Den muscles by returning their protein synthesis rates to levels similar to Sham muscles. These data indicate that Rsv directly inhibits the proteolytic activity of lysosomal and ubiquitin-proteasome systems, mainly in Den muscles through, at least in part, the activation of PKA/CREB signaling.